PARE0015 The importance of face-to-face networks: findings from the 2nd eular young pare conference, "change the future". (15th June 2017) - Andersen, J; Balazova, P; Olsder, W; Ostuzzi, S; Papastavrou, D; Stones, S; Wilhelmer, T; Boyd, P; ,
Abstract : Background: EULAR Young PARE's strategy for 2020 is to establish and strengthen groups for young people with rheumatic and musculoskeletal diseases (RMDs) across Europe, by developing a collaborative network. We aim to empower youth leaders to ensure the voice of young people with RMDs is heard. To facilitate this, the 2nd EULAR Young PARE Conference was held in Retie, Belgium in October 2016. Objectives: To empower and educate EULAR Young PARE youth liaisons, focusing on developing academic and interpersonal skills to best support young people across Europe living with RMDs. This was achieved through a series of practical, skills-based workshops and plenary sessions. Methods: The EULAR Young PARE working group reflected on the conference during a debrief meeting. A post-conference evaluation was completed by liaisons. A five-point Likert scale (1= very bad, 5= very good) was used alongside open questions. In addition, there was an informal meeting to generate discussions and receive input from participants regarding the future direction and focus of EULAR Young PARE in 2017 and 2018. Results: The conference was attended by 22 youth liaisons from 20 organisations. The programme was well received with the face-to-face interactions favoured to establish and grow collaborative networks. Through a series of digital poster presentations, each liaison had the opportunity to share recent work in their national organisations. This session was evaluated positively and encouraged liaisons to identify opportunities for collaboration and new national activities, using the VKC as a platform for the sharing of best practices. Workshops were delivered in collaboration with EMEUNET and a EULAR member organisation representative and we piloted a series of six walk-in workshops. While these workshops were evaluated positively, a lack of structure and the need for time constraints was a consistent finding. Conclusions: The "Change the Future" conference was a successful meeting of youth liaisons from across Europe, who were highly satisfied with the programme and mechanism of delivery. Meeting in person facilitated the growth and continued involvement within the EULAR Young PARE network. The activities of EULAR, and specifically the Standing Committee of PARE, were shared with liaisons, encouraging liaisons to become involved in a wider number of EULAR activities. Theoretical and practical skills were developed, while best practices and experiences were shared and highly valued. Furthermore, in future conferences, bitesize workshops will replace walk-in workshops for structure and clarity. Despite living in a digitally connected world, face-to-face interactions cannot be replaced. Learning can be enhanced and actions implemented when motivated individuals are physically united, demonstrating the need for the use of multiple meeting methods to drive innovation. Following the conference, everyone felt inspired, empowered and motivated to implement concrete and tangible steps to inform ongoing and future work. Together, we can change the future for young people living with RMDs. Disclosure of Interest: None declared